Therapeutic Anticoagulation May Be Associated with Reduced 14-day Mortality in Mechanically Ventilated Patients with COVID-19 - Randi Jenkins; Sahil Sheth; Breanne Nestor; Adrien Mazer (University of Minnesota Libraries Publishing, 2021)
Purpose: To assess the impact of therapeutic dose versus prophylactic dose anticoagulation regimens on outcomes in mechanically ventilated patients with COVID-19. Methods: We performed a retrospective cohort analysis of consecutive mechanically ventilated adult patients with COVID-19 admitted to the intensive care unit (ICU) and initiated on anticoagulation from February 1st to May 31st, 2020. The primary endpoint was 14-day mortality. Secondary endpoints included 30-day mortality, hospital length of stay (LOS), duration of mechanical ventilation, major bleeding, and new thromboembolic event. Results: Of the 121 mechanically ventilated patients with COVID-19, 33 in the therapeutic-dose group and 34 patients in the prophylactic-dose group were included in the final analysis. The therapeutic-dose group had a decreased 14-day mortality compared to the prophylaxis dose group (9.1% vs 41.2%, p=0.004). In addition, 30-day mortality was also lower in the therapeutic anticoagulation group (24.2% vs. 52.9%, p=0.024). A longer hospital LOS (45.7 vs 26 days, p=0.003) and duration of mechanical ventilation (33.9 vs 13.3 days, p<0.001) were observed in patients on therapeutic anticoagulation in comparison to the prophylaxis dosing group. A higher rate of major bleeding was observed in patients who received therapeutic anticoagulation.   Conclusion: In this analysis of mechanically ventilated COVID-19 patients in the ICU, therapeutic dose anticoagulation was associated with a significantly lower 14-day mortality, but increased bleeding.